Peran Perceived Organizational Support dalam Memediasi Pengaruh Talent Management terhadap Retensi Karyawan di Montigo Resort Seminyak Bali - I Kadek Agus Budi Mahendra; I Gusti Ayu Manuati Dewi (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
This research aims to explain the direct effect of talent management on employee retention and perceived organizational support and indirect effect of talent management on employee retention through perceived organizational support. Theory referred in this study is Social Exchange Theory. The sample in the study was 73 employees determined by purposive sampling (saturated sample). The data collected by interview and questionnaires. Technoque of analysis used in this study was Path Analysis. The findings show that talent management has a positive and significant effect on employee retention and perceived organizational support, perceived organizational support has a positive and significant effect on employee retention and talent management has an indirect effect on employee retention through perceived organizational support. The implication of this study is the leader of Montigo Resort Seminyak-Bali supposed to improve talent management and increase organization support to improve the retention of employees.